Issuer Operating Performance and IPO Price Formation - WILLENBORG, MICHAEL; WU, BIYU; YANG, YANHUA SUNNY (Journal of Accounting Research, 2015)
ABSTRACT We study the relation between issuer operating performance and initial public offering (IPO) price formation from the initial price range to the offer price to the closing price on the first trading day. For a post‐bubble sample of 2001–2013 IPOs, we find that pre‐IPO net income and, in particular, operating cash flow are strongly, positively associated with the revision from the mid‐point of the initial price range to the offer price and that the “partial adjustment phenomenon” concentrates among issuers with the strongest operating performance. As for why publicly observable information helps predict changes in valuation from when the initial price range is set to when the offer price is set, our findings suggest that strong‐performing issuers, especially those offering small slices of ownership, have lower bargaining incentives and are susceptible to the underwriter(s) low‐balling the price range. Overall, our results suggest an important role for accounting information in understanding the pricing of book‐built IPOs and are consistent with the presence of agency problems between issuers and underwriters.